Clinical outcome of patients with ST-elevation myocardial infarction and angiographic evidence of coronary artery ectasia. (25th November 2020) - Silverio, A; Esposito, L; Fierro, G; Di Maio, M; Di Feo, F; Iannicelli, A; Varone, M; Vigorito, F; Maione, A; Di Muro, M.R; Attisano, T; Vecchione, C; et al.
Abstract: Background: Coronary artery ectasia (CAE) is a relatively frequent finding in patient with ST-elevation myocardial infarction (STEMI) who undergo emergent coronary angiography. However, the long-term outcome of STEMI patients with CAE as compared to Non-CAE has been poorly investigated. Purpose: To compare the baseline features and outcome of patients with and without CAE in the clinical setting of STEMI. Methods: All patients with STEMI who underwent emergent coronary angiography from January 2012 to December 2017 at our Institution were retrospectively enrolled. Baseline demographic, clinical, instrumental, angiographic and percutaneous coronary intervention (PCI) findings were collected for patients with and without CAE. The study outcome measures were recurrent myocardial infarction (MI) and all-cause death. The propensity score weighting (PSW) technique was used to take into account for potential selection bias in treatment assignment between CAE and Non-CAE groups. Results: The study included 534 patients with STEMI (mean age 62.9±12.0 years), 154 were CAE and 380 Non-CAE. The two groups were significantly different in terms of sex (90.9% in CAE vs 72, 6% in Non-CAE, p<0.001), diabetes (11.7% vs. 25.8%; p=0.009) and smoking status (72.1% vs. 62.4%; p=0.042). The right coronary artery was more commonly treated in CAE patients (41.6% vs. 30.8%, p=0.023) and, as expected, the stent diameter (p<0.001) and the TIMI frame count (p<0.001) were significantly higher in CAE group. The myocardial blush grade was higher in Non-CAE (p<0.001). The Kaplan-Meyer analysis showed a comparable rate of all-cause death among the two groups (3.4/100 person/years in CAE vs. 3.5 per 100 person/years in Non-CAE, Log-Rank = 0.86). The survival free from recurrent MI was lower, although not statistically significant, in CAE vs. Non-CAE patients (3.1/100 person/years vs. 4.8/100 person/years; Log-Rank = 0.068). After PSW, an optimal balance was obtained as demonstrated by a standardized mean difference <0.1 for all the variables included in the model. The adjusted Cox regression analysis showed a significantly higher risk of recurrent MI in CAE vs. Non-CAE groups (HR = 1.93; p=0.009). No difference in the risk of all-cause death was observed (HR = 0.83, p=0.501). Conclusions: Patient with STEMI and angiographic evidence of CAE have a different clinical profile compared to Non-CAE. In this analysis focused on STEMI patients, CAE was associated with a higher risk of recurrent MI at long-term follow-up. Funding Acknowledgement: Type of funding source: None